2019
DOI: 10.3390/ijms20143562
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Alleviates Rotavirus Infection through a Microrna-155-5p Mediated Regulation of the TBK1/IRF3 Signaling Pathway In Vivo and In Vitro

Abstract: (1) Background: Vitamin D (VD) plays a vital role in anti-viral innate immunity. However, the role of VD in anti-rotavirus and its mechanism is still unclear. The present study was performed to investigate whether VD alleviates rotavirus (RV) infection through a microRNA-155-5p (miR-155-5p)-mediated regulation of TANK-binding kinase 1 (TBK1)/interferon regulatory factors 3 (IRF3) signaling pathway in vivo and in vitro. (2) Methods: The efficacy of VD treatment was evaluated in DLY pig and IPEC-J2. Dual-lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 62 publications
(82 reference statements)
0
34
0
2
Order By: Relevance
“…In a mouse model, LL-37 reduced influenza A virus replication [27]. In another laboratory study, 1,25(OH) 2 D reduced the replication of rotavirus both in vitro and in vivo by another process [28]. A clinical trial reported that supplementation with 4000 IU/d of vitamin D decreased dengue virus infection [29].…”
Section: Vitamin D and Mechanisms To Reduce Microbial Infectionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a mouse model, LL-37 reduced influenza A virus replication [27]. In another laboratory study, 1,25(OH) 2 D reduced the replication of rotavirus both in vitro and in vivo by another process [28]. A clinical trial reported that supplementation with 4000 IU/d of vitamin D decreased dengue virus infection [29].…”
Section: Vitamin D and Mechanisms To Reduce Microbial Infectionsmentioning
confidence: 98%
“…RSV Demonstrated that the human cathelicidin LL-37 has effective antiviral activity against RSV in vitro and prevented virus-induced cell death in epithelial cultures, [114] RSV Performed a laboratory study that identified the mechanism by which vitamin D reduced risk of RSV. [28] RSV Found that the T-allele of the vitamin D receptor has a lower prevalence in African populations and runs parallel to the lower incidence of RSV-associated severe ALRI in African children, 1 year.…”
Section: H9n2 Influenzamentioning
confidence: 99%
“…In a mouse model, LL-37 reduced influenza A virus replication [27]. In another laboratory study, 1,25(OH)2D reduced replication of rotavirus both in vitro and in vivo by another process [28]. A clinical trial reported that supplementation with 4000 IU/d of vitamin D decreased dengue virus infection [29].…”
Section: Vitamin D and Mechanisms To Reduce Microbial Infectionsmentioning
confidence: 98%
“…VD 3 was also able to attenuate rotavirus infection by regulating autophagic maturation and cathelicidin gene expression in IPEC-J2 cells infected with porcine rotavirus [174]. 1,25(OH) 2 D 3 also alleviated rotavirus infection through the miRNA-155-5p-mediated regulation of the TANK-binding kinase (TBK)1/interferon-responsive factor (IRF) 3 signaling pathway [175]. In line with this, VD supplementation alleviated intestinal damage and protected against inflammation in pigs infected with porcine epidemic diarrhea virus (PEDV) [176].…”
Section: Rotavirusmentioning
confidence: 99%